2014
DOI: 10.1038/jid.2013.540
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Increase in Regulatory T Cells Controls Development of Vitiligo

Abstract: T cell cytolytic activity targeting epidermal melanocyte is shown to cause progressive depigmentation and autoimmune vitiligo. Using the recently developed transgenic mice h3TA2 that carry T cell with a HLA-A2 restricted human tyrosinase reactive TCR and develop spontaneous vitiligo from an early age, we addressed the mechanism regulating autoimmune vitiligo. Depigmentation was significantly impaired only in IFN-γ knockout h3TA2 mice but not in TNF-α or perforin knockout h3TA2 mouse strains, confirming a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 42 publications
5
84
0
3
Order By: Relevance
“…Detailed protocols for staining the cells for surface markers and intracellular cytokines have been described earlier (15), and in supplementary methods. Detailed methodology for q-PCR is provided in supplementary method section.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed protocols for staining the cells for surface markers and intracellular cytokines have been described earlier (15), and in supplementary methods. Detailed methodology for q-PCR is provided in supplementary method section.…”
Section: Methodsmentioning
confidence: 99%
“…This trend was also seen after antigen-specific TCR stimulation with cognate peptide (p<0.01). Additionally, there were increased numbers of IL-17+ T cells seen infiltrating the skin of these mice (p<0.01)[68]. …”
Section: Il-17 Dynamics In Vitiligomentioning
confidence: 99%
“…Recently, Chatterjee et al [81] have reported the first animal study proposing Tregs as a therapeutic for vitiligo. Using transgenic mice that carry T cells with a human leukocyte antigen (HLA)-A2-restricted human tyrosinase peptide-reactive T cell receptor and that develop spontaneous vitiligo from an early age, adoptively transferred Tregs were found to induce a lasting remission of vitiligo in mice treated at the onset of disease, or in mice with established disease.…”
Section: Adoptive Transfer Therapy Using Regulatory T Cellsmentioning
confidence: 99%